CHOLEDOCAL CYST Pada DEWASA: PERAN ULTRASONOGRAFI - Valinia K, Priska; Prawita M, Indira (Cendana Medical Journal, 2022)
Choledocal cyst (CC) is a rare congenital cystic dilatation of bile duct. The etiology is unknown, and likely multifactorial and it is uncertain whether they are congenital or acquired. Ultrasonography is initial imaging which can be used to evaluate biliary system. We report 43 year old female presented with icteric for 3 months. She had dark-color urine and white stool. She didn’t complain about abdominal pain or palpable mass in her abdomen.We performed ultrasonography and found dilatation of common bile duct for ± 7.4 cm. Gall bladder and another intrahepatic structures were normal. The patient was referred to digestive surgeon in adequate facility. Conclusion: Ultrasonography is initial and non-invasive imaging for viewing biliary system. Early detection and management can prevent morbidity and improve patient’s quality of life.